COVID-20 DAN SEPILAHAN FIKSI LAINNYA SEBAGAI BENTUK SASTRA DISTOPIA - Dwi Rahariyoso; Dimas Sanjaya (Universitas Sarjanawiyata Tamansiswa, 2020)
This article discusses the literary narrative of dystopia in Covid-20 and Other Sorts of Fiction. This study aims to determine the formulation of dystopia and discourse short stories offered in Covid-20 and Other Fiction. This research is a qualitative descriptive study with the postmodernism approach of Jean-Francois Lyotard. For data collection with literature study. To analyze the data using the descriptive analysis method. The research results found that dystopian literature provides formulations in it, namely, the time landscape (the future of the world and the Divine), catastrophic situations (dehumanization, chaos), coveted transformations, in which a new but unpleasant world is created due to social degeneration, an order. destructive social activities, or the consequences of social transformation efforts that lead to disasters.